Historic Total Fertility Rates of Sri Lanka (1960 – 2021) and Future Trends - De Silva, K.T. N.; Kuruppuge, H.W.; Manel, D.P.K. (My University, 2024)
Fertility is one of the key components that determine the population change in Sri Lanka. Total Fertility Rates (TFR) are the average number of children a woman would have by the end of her childbearing years (15-49) if she bore children at the current age-specific fertility rates. The average has been declining over the past decade in Sri Lanka. It is essential to understand the trends and patterns of TFR in that aspect to enhance the quality of predetermined long-term economic, health and educational plans as well the policy implements in the country. The main objective of the study is to identify the trends and patterns of historic Total Fertility Rates of Sri Lanka (1960 – 2021) and future trends. The study carries out based on the secondary data on TFR extracted from World Bank data (1960-2021). Initially, the univariate time series analysis was utilized to identify the pattern of TFR using the R Statistical software. This study revealed that there is a decreasing future trend in TFR using ARIMA (1, 2, 1) model which was fitted as the best model to forecast the future behavior TFR. The fitted model was. The forecasted TFR values for the period from 2022 to 2026 were 1.9577, 1.9372, 1.9167, 1.8963 and 1.8758 respectively. It is suggested to have a comparative study on fertility trends and patterns with consideration of socioeconomic and cultural factors in Sri Lanka since TFR varies due to socioeconomic and cultural diversity.
Keywords: Age Specific Fertility Rate, ARIMA model, Total Fertility Rate, Univariate time series analysis